Decisions on extending group membership: Evidence from a public good experiment - Christian Grund; Christine Harbring; Kirsten Thommes; Katja Rebecca Tilkes (Games, 2020)
We experimentally compare the consequences for group cooperation of two decision mechanisms involving the extension of group membership. We analyze an exogenous decision (random draw) and an endogenous decision (made by a particular group member) mechanism to extend a temporary agent's group membership. Our results reveal that the prospect of group membership extension affects not only the temporary but also the permanent group members' contributions with an endogenous mechanism.
Keywords: 330; cooperation; experiment; group membership; public good game